A healthy diet is costly, but even with limited income Kenyans can eat better - Ecker, Olivier; Comstock, Andrew R.; Pauw, Karl (International Food Policy Research Institute, 2023)
Four important implications for policy to promote and guide a transformation toward healthy diets for all Kenyans can be drawn from this research: First, Kenya’s diet problem — the underconsumption of nutritious foods and increasingly high consumption of calorie-rich but micronutrient-sparse foods — is primarily a poverty problem. Most Kenyans simply cannot afford a healthy diet. Accelerated poverty reduction will have important nutritional benefits. Second, there are large differences between the costs of meeting dietary guidelines for highly nutritious foods and the costs of obtaining adequate amounts of calorie-dense staple foods. These cost gaps have a strong effect on household diets because the food choices of many Kenyan households are primarily driven by a need to satisfy calorie requirements. This points to a problem of relative food prices, which interacts with the poverty problem. It is most apparent for animal-source protein foods and, to a lesser degree, for vegetables. Thus, policy interventions and technological innovations that address this relative food price problem are needed to narrow the consumption gaps for nutritious food groups, particularly animal-source foods and vegetables. Third, the food preferences of Kenyans show that the poor-quality diets consumed by many households are not solely due to insufficient purchasing power and high prices for nutritious foods. This is most obvious for plant-based protein foods — pulses and nuts — which have low prices per calorie, but which few households consume in sufficient amounts to meet the recommended healthy intake. This weak consumer preference for such foods suggests a lack of knowledge of their nutritional value and their importance for healthy diets. Nutrition education may aid in changing consumer behavior to increase the consumption of pulses and nuts, as well as other nutritious foods that are now underconsumed relative to the healthy reference diet. Kenyans can consume more healthy diets with their current incomes. While healthy diets are costly for many Kenyan households, changes can be made in the current typical diet to achieve better and more balanced nutrient intake at the same cost. Finally, policies aimed at promoting food systems transformation in Kenya should factor in the dietary needs of Kenyans. As agriculture is the dominant sector in Kenya’s food systems, a balance must be found between traditional objectives including productivity growth, export stimulation, and farmer support, on the one hand, and the new responsibility of improving the availability of nutrient-dense foods for better nutrition and health for all Kenyans, on the other.